High Seroprevalence of Severe Fever with Thrombocytopenia Syndrome Virus Infection among the Dog Population in Thailand - Ishijima, Keita; Phichitraslip, Thanmaporn; Naimon, Nattakarn; Ploypichai, Preeyaporn; Kriebkajon, Benyapa; Chinarak, Torntun; Sridaphan, Jirasin; Kritiyakan, Anamika; Prasertsincharoen, Noppadol; Jittapalapong, Sathaporn; Tangcham, Kanate; Rerkamnuaychoke, Worawut; et al. (Viruses, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonotic disease caused by the SFTS virus (SFTSV). In Thailand, three human cases of SFTS were reported in 2019 and 2020, but there was no report of SFTSV infection in animals. Our study revealed that at least 16.6% of dogs in Thailand were seropositive for SFTSV infection, and the SFTSV-positive dogs were found in several districts in Thailand. Additionally, more than 70% of the serum samples collected at one shelter possessed virus-neutralization antibodies against SFTSV and the near-complete genome sequences of the SFTSV were determined from one dog in the shelter. The dog SFTSV was genetically close to those from Thailand and Chinese patients and belonged to genotype J3. These results indicated that SFTSV has already spread among animals in Thailand.